2020
DOI: 10.33059/jsb.v3i1.2207
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Tokoh Dan Penokohan Dalam Novel Keajaiban Adam Karya Gusti M Fabiano Tahun 2019

Abstract: Penelitian ini bertujuan untuk mendeskripsikan tokoh dan penokohan dalam novel Keajaiban Adam karya Gusti M Fabiano. Metode yang digunakan dalam penelitian ini menggunakan metode deskriptif analitik. Sumber data diperoleh dari novel Keajaiban Adam yang berkaitan dengan tokoh dan penokohan. Pada penelitian ini, peneliti menggunakan metode dokumentasi dalam pengumpulan data. Hasil analisis yang telah didapatkan dalam novel Keajaiban Adam karya Gusti M Fabiano menunjukkan bahwa pengarang memunculkan dua puluh tig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Characterizations according to Jones (Renmaur & Rutumalessy, 2020), are depicting a clear picture of someone who is shown in a story. According to Abrams (Mardhiah et al, 2020) story characters (characters) are people who are shown in a narrative or drama work, which the reader interprets as having certain moral qualities and tendencies as expressed in speech and action.…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Characterizations according to Jones (Renmaur & Rutumalessy, 2020), are depicting a clear picture of someone who is shown in a story. According to Abrams (Mardhiah et al, 2020) story characters (characters) are people who are shown in a narrative or drama work, which the reader interprets as having certain moral qualities and tendencies as expressed in speech and action.…”
Section: Characterizationmentioning
confidence: 99%
“…Based on researches related to moral values of characters and characters in a film, it was found that there is a delivery of meaning and moral values to the audience in a film (Andriani & Abidin, 2020) while the film that has been studied previously is the film The Boss Baby (Lukmantoro et al, 2019), the animated film Moana (Fatriyah et al, 2020), the novel miracle of Adam (Mardhiah et al, 2020), the room movie (Hidayat & Indarujati, 2020), the film Habibie and Ainun (Ahmadi, 2019). Therefore, this study aims to determine the moral values of Nobita's character in the film Stand By Me Doraemon 2 through film subtitles.…”
Section: Introductionmentioning
confidence: 99%
“…Karya sastra pada pembahasan kali ini yaitu karya sastra perfilman animasi tentunya akan terdapat tokoh di dalam ceritanya. Seorang tokoh di dalam sebuah cerita sama seperti manusia pada umumnya pastinya selalu memiliki watak tertentu (Mardhiah et al, 2020) Tokoh yang terdapat di dalam sebuah cerita diketahui seperti manusia biasa pada umumnya dan tokoh pun memiliki watak yang beragam. Dengan adanya beragam watak dan sifat dari tokoh ini, tentu akan memungkinkan terjadinya konflik di dalamnya.…”
Section: Pendahuluanunclassified